2017
DOI: 10.1007/s13577-017-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei strain 06TCa19 suppresses inflammatory chemokine induced by Helicobacter pylori in human gastric epithelial cells

Abstract: Helicobacter (H.) pylori infection is an important risk factor for gastric cancer that causes gastric inflammation. Inflammatory chemokines such as interleukin (IL)-8 and regulated on activation normal T cell expressed and secreted (RANTES) are elevated in the gastric mucosa by H. pylori. This study aimed to investigate the effects of Lactobacillus paracasei strain 06TCa19, a probiotic strain, on IL-8 and RANTES expression and production induced by H. pylori using human gastric epithelial cell lines. Strain 06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
(43 reference statements)
0
17
0
3
Order By: Relevance
“…This activity of probiotics may not only affect P. gingivalis colonization levels, but may also prevent the mechanisms by which this keystone pathogen favors the growth of the entire microbial community and leads to dysbiosis by promoting a localized chemokine paralysis . A recent study revealed that co‐culture of L. paracasei and human gastric epithelial cell lines infected with H. pylori resulted in decreased adhesion and reduced CXCL8 expression, which is elevated in the gastric mucosa by Helicobacter pylory . This difference clearly illustrates that probiotics modulatory properties should be explored according to the imbalance in innate response induced by specific pathogens on mucosa surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This activity of probiotics may not only affect P. gingivalis colonization levels, but may also prevent the mechanisms by which this keystone pathogen favors the growth of the entire microbial community and leads to dysbiosis by promoting a localized chemokine paralysis . A recent study revealed that co‐culture of L. paracasei and human gastric epithelial cell lines infected with H. pylori resulted in decreased adhesion and reduced CXCL8 expression, which is elevated in the gastric mucosa by Helicobacter pylory . This difference clearly illustrates that probiotics modulatory properties should be explored according to the imbalance in innate response induced by specific pathogens on mucosa surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Cats et al, (2003) found that culture and supernatants from L. casei grown in MRS medium significantly induced clear inhibition zone of H. pylori. Also, another study found that use of L. paracasei strain 06TCa19 may prevent H. pylori associated gastric inflammation (Takeda et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…[13,61] Most effective strain of probiotics has not been determined yet for the management of H pylori infection, but Lactobacillus species showed proven efficacy because they are resistant to acidic environment, pancreatic enzyme, and bile salts and release lactic acid inhibiting the adhesion of H pylori to the cells. [43,6264] In our study, L paracasei was used because it can produce a remarkable amount of lactic acid, which is regarded as the origin of anti- H pylori activity, [65] and has better immunomodulatory function in preventing intestinal inflammation than L plantarum or L rhamnosus . [16,66] Furthermore, L paracasei inhibited the elevation of IL-8 and regulated upon activation, normal T-cell expressed and presumably secreted (RANTES) released from the H pylori -infected gastric epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…[16,66] Furthermore, L paracasei inhibited the elevation of IL-8 and regulated upon activation, normal T-cell expressed and presumably secreted (RANTES) released from the H pylori -infected gastric epithelium. [62,67]…”
Section: Discussionmentioning
confidence: 99%